Integrative review: palliative care in oncological patients (Research, Society and Development, 2020)
Palliative care is offered to patients with no chance of cure to have a higher quality of life until their death arrives. Nursing is a field of health that has been growing gradually in recent years and improving with regard to palliative cancer care, generating new comfort techniques for the patient. Therefore, the objective was to know the palliative care used in cancer patients provided by the nursing staff through an integrative review, whose data were collected by the Scielo database from 2009 to 2019, with the following descriptors: Palliative Care, Cancer and nursing care. Data were analyzed through Content Analysis. It was founded 20 articles on the subject and this study included 8 articles. As an innovative approach, palliative care brings its importance within the care provided to hospitalized patients and the need for knowledge of the professional nurse and their training about humanized care. It was observed that palliative care when practiced by the nurse is given greater comfort and pain relief to the patient. There was a deficit in training during the graduation of the professional nurse.